iMSL Interactive Malay Sign Language Courseware for the Deaf and Hearing Impaired - Nur Tahrina, Abdullah (2012)
Malay Sign Language (MSL) or Bahasa Isyarat Malaysia is a language that has been used by the deaf people in Malaysia. The deaf and hearing-impaired people go to special schools to learn MSL. In current age, technology could be utilized for the purpose of providing MSL course for the hearing-impaired people and their stakeholders. With the provision of the technology based MSL course, learning MSL not only happen in schools, but also at home, or anywhere. This makes the learning activity pervasive. Based on that argument, this study aims at proposing a model for an interactive multimedia courseware which is called iMSL. Accordingly, this paper discusses the background concept for the needs and design of the iMSL. The objectives of the study include 1) To determine the interface necessity for the iMSL for the deaf and hearingimpaired, 2) To design and developed the iMSL, and 3) To evaluate the usefulness of iMSL through user testing. In accomplishing this study, Waterfall Methodology was adapted. There are involved three phase which are User Requirements, Prototype Development and finally the Testing and Evaluation phase. ADDIE Model also adapted in developing prototype of iMSL. The qualitative approaches such as observation and interview were conducted with four students in standard 1. The result of this study concluded that the technology based on courseware is an alternative tool that can be used to assist the learning process for the deaf and hearing-impaired students. It is easy to understand and help teacher to teach in interesting way.